Kupas Tuntas : Rahasia Dibalik Konsep Penghapusan Hukum Ayat dalam Al-Qur’an - Hasbullah, Irma Juliana; Husna, Zulfaniyatul; Sohrah, Sohrah; Miswar, Andi (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
The Qur'an is the primary guidance for Muslims and holds a crucial role, especially among scholars. However, within the field of Islamic studies, there are views suggesting that certain verses in the Qur'an seem textually contradictory. This phenomenon has led to the study of nasikh-mansukh, a theory aimed at understanding verses perceived as conflicting by explaining the concept of abrogation or replacement of rulings in divine revelation. Nonetheless, the concept of nasikh-mansukh is not universally accepted by all scholars or Qur'anic experts. Most agree that the Qur'an is a perfect holy scripture without revisions. These differing views reflect the diversity of perspectives within the Islamic scholarly tradition. This study employs a qualitative method using library research. It analyzes the concept and types of naskh, evidence for its establishment, differing opinions about naskh, its scope, controversies among scholars, and the wisdom that can be drawn from studying this theory. The findings indicate that differences of opinion among scholars are often rooted in foundational issues, such as perspectives or interpretative methods applied. By understanding the theory of nasikh-mansukh, Muslims can gain deeper insight into how seemingly contradictory verses can be reconciled. Moreover, this study underscores the importance of knowledge in interpreting sacred texts, thereby strengthening faith in the Qur'an's perfection as the final revelation of Allah SWT.